2021
DOI: 10.5334/ijic.5508
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Primary and Secondary Care to Enhance Chronic Disease Management: A Scoping Review

Abstract: Background: In Ireland, as in many healthcare systems, health policy has committed to delivering an integrated model of care to address the increasing burden of chronic disease. Integrated care is an approach to healthcare systems delivery that aims to minimise fragmentation of patient services and improve care continuity. To this end, how best to integrate primary and secondary care is a challenge. This paper aims to undertake a scoping review of empirical work on the integration of primary and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…longer patient lists and more home and office visits [ 9 , 10 ]. The same lack of evidence is observed in the international literature [ 11 , 12 ]. In the rest of this paper, we will consider GPs’ participation in MGP as our variable of interest indicating an (institutional) marker of integrated practices.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…longer patient lists and more home and office visits [ 9 , 10 ]. The same lack of evidence is observed in the international literature [ 11 , 12 ]. In the rest of this paper, we will consider GPs’ participation in MGP as our variable of interest indicating an (institutional) marker of integrated practices.…”
Section: Introductionsupporting
confidence: 62%
“…This research has both strengths and weaknesses. The main strength consisted in being able to demonstrate that the MGP organizational formula (the French way to obtain the integration of primary care) was also beneficial to patients, at least to those with chronic conditions, and not only to healthcare professionals - there are more results in the literature demonstrating that latter point, while only a few were really able to deal with patients’ outcomes [ 12 ]. In our view, the choice of the lockdown as an observation period was especially relevant, as it was a period of severe stress for the entire healthcare system, and one which gave us the opportunity to verify the good functioning of the system when presented with real challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified three specific interventions to enhance integration of care for chronic-disease patients: eHealth interventions, multidisciplinary teams, and education of healthcare professionals. Importantly, the authors state that an ineffective electronic integration process does not have a neutral effect but rather hinders integration of care (Murtagh et al, 2021). Other Irish research also identified integration and investment in HIS and EHRs as key for chronic obstructive pulmonary disease (COPD) patients (Boland et al, 2015;Ferrone et al, 2019).…”
Section: Using His and Big Data To Learn Understand And Inform Decision-makingmentioning
confidence: 99%
“…Sláintecare, Ireland's strategy for healthcare reform, puts a clear emphasis on the need to change the model of care for those with chronic illness, and the importance of HIS and health technologies for doing so (Department of Health, 2019;Government of Ireland, 2018; Houses of the Oireachtas Committee on the Future of Healthcare, 2017). A recent review by Irish researchers examined the literature on the integration of primary and hospital care to enhance chronic-disease management understandings for Ireland (Murtagh et al, 2021). The authors identified three specific interventions to enhance integration of care for chronic-disease patients: eHealth interventions, multidisciplinary teams, and education of healthcare professionals.…”
Section: Using His and Big Data To Learn Understand And Inform Decision-makingmentioning
confidence: 99%
“…Fragmented services are a challenge in several countries [ 7 8 9 10 11 12 13 14 15 16 17 ], and better integration of care is needed [ 4 9 18 19 20 21 22 ]. Integration can be achieved in various ways [ 23 24 25 26 27 ], such as through multidisciplinary teams [ 18 23 28 29 30 ]. Flexible Assertive Community Treatment (FACT) is a multidisciplinary team model that is used in several countries [ 11 31 32 33 34 35 36 37 ] and aims to provide integrated care for people with severe mental illness [ 38 ].…”
Section: Introductionmentioning
confidence: 99%